(Too many) mathematical models of circadian clocks (?) - Lema, M. A. (2001)
Many mathematical models derived from the principles obtained from empirical observations in chronobiology have been proposed and explored. They cover several organisms and phenomena, and utilize quite different formal approaches. These models can be divided into the ones that intend to describe pacemaker core function, such the Goodwin-oscillator family, non-genetic approaches or purely mathematical (i.e., without clear biochemical correlations) models, and the ones that represent events depending on pacemaker activity, i.e., photoperiodic phenomena. We aim to illustrate the diversity of mathematical and methodological approaches to describe circadian systems and related matters.